Impact of goat population management strategies on goat meat production in Bangladesh (Bangladesh Journal of Livestock Research, 2020)
To increase goat-meat production, this study has been aimed to evaluate goat-meat production potentiality using different management strategies of goat-population rather than goat-meat productivity management in Bangladesh. Simulation Matrix (SIMM) model was used under three scenarios of goat-population management strategies such as Scenario1(Base rate): 2 kids/year production with 30% kid mortality, Scenario 2: Production of 6 kids/year with 30% kid mortality and Scenario 3: Production of 6 kids/year with 10% kid mortality to analyze their impact on goat-meat production in Bangladesh. Results showed on average only 270.09 thousand ton /year of goat-meat can produce at the existing rate (2 kids Production/year with 30% kid mortality). If it is possible to increase kid production up to 6 then can produce on average 23714.4 thousand ton/year of goat-meat. Further, it is possible to reduce the kid mortality rate up to 10%, goat-meat is the highest 932430.0 thousand ton/year. Result indicated a great positive impact of goat-population management strategies on goat-meat production. Therefore, 10% kid mortality rate with 6 kids/year production of goat-population management could be suitable management or best strategy for higher goat-meat production in Bangladesh.Bangladesh J. of Livestock Res. 21-25: 118-126, 2018